2006
DOI: 10.1001/archsurg.141.1.43
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind Randomized Controlled Trial of Toremifen Therapy for Mastalgia

Abstract: Hypothesis: Toremifen is effective in reducing breast pain and does not increase the incidence of adverse events as a therapy for moderate to severe mastalgia. Design and Patients:In a double-blind randomized controlled trial, patients with moderate to severe mastalgia received toremifen citrate, 30 mg daily, or a placebo tablet for 3 menstrual cycles and were followed up for breast pain score and adverse events. The serum levels of estradiol, progesterone, and prolactin were examined before treatment and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…As is widely known, AIs are harmful for premenopausal patients. However, with respect to toremifene clinical trials have shown that toremifene does not increase the incidence of adverse events for moderate to severe mastalgia patients [40]. Other reports have shown that toremifene (60 mg daily) has no substantial negative effects on bone mineral density in pre- or postmenopausal women and may actually have a minor favorable influence [41].…”
Section: Discussionmentioning
confidence: 99%
“…As is widely known, AIs are harmful for premenopausal patients. However, with respect to toremifene clinical trials have shown that toremifene does not increase the incidence of adverse events for moderate to severe mastalgia patients [40]. Other reports have shown that toremifene (60 mg daily) has no substantial negative effects on bone mineral density in pre- or postmenopausal women and may actually have a minor favorable influence [41].…”
Section: Discussionmentioning
confidence: 99%
“…Toremifene is effective to treat mastalgia in some small phase II trials [126, 127], and is also effective at decreasing prostate cancer incidences in a high-risk population [128]. In addition, a recent multicenter randomized phase III trial showed that toremifene increased bone density and improved lipid profile in men receiving androgen deprivation therapy for prostate cancer [129, 130].…”
Section: New Sermsmentioning
confidence: 99%
“…4 In a randomised controlled trial (RCT) (n = 195), levels of serum oestradiol in women with untreated cyclical mastalgia were higher than in women with noncyclical mastalgia. 5 The role of elevated oestrogen in mastalgia is plausible due to its physiological effect on normal breast tissue (stimulates cellular proliferation). In contrast, a smaller study of women with benign breast disease (n = 17) found that oestradiol, progesterone, thyroid hormone and thyrotropin levels were normal.…”
Section: Hormone Dependantmentioning
confidence: 99%
“…However, this mechanism conflicts with literature that suggests elevated levels of oestrogen cause mastalgia. 5,25 Breast size It has been suggested that the weight of breasts creates weakness and strain on the suspensory ligaments, thus creating discomfort. No research has directly explored the role of breast size and mastalgia; however, a survey examined the role of mastalgia on exercise behaviour in 1397 women who ran the 2012 London Marathon and identified, as secondary outcomes, that one-third of women who did experience breast pain had larger breast size.…”
Section: Methylxanthinesmentioning
confidence: 99%
See 1 more Smart Citation